Corsuccio da Sascorbaro and its "Vermicello dalla seta" (Bollettino di zoologia agraria e bachicoltura, 2024)
Corsuccio da Sascorbaro's studies are reported. This Author, already in 1581 gave useful and accurate informations on silkworm breeding.
Keywords: Corsuccio da Sascorbaro; Verrnicello dalla seta; Bombyx mori; silk worm